2016
DOI: 10.1002/apj.1970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air distribution on furnace temperature and CO/NO/N2O/SO2 emissions in a lab‐scale CFB furnace cofiring both biomass/coal and petroleum coke/coal

Abstract: The effects of air distribution (excess ratio of primary air, ERPA; excess ratio of secondary air, ERSA; and excess ratio of total air, ERTA) on furnace temperature and CO/NO/N 2 O/SO 2 emissions were systematically studied in a 0.2 MW lab-scale circulating fluidized bed (CFB) furnace cofiring both biomass/coal and petroleum coke/coal. Unlike the ERSA, the high ERPA proved to be conducive to an even temperature distribution along the height of the furnace. As a result of the interaction of the heat release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The concentration of pollutants in the flue gas is based on there being 6 Vol.% O 2 in the flue gas and this is expressed in mg/Nm 3 (on the dry basis). Detailed descriptions are available in the references (Wang et al , 2016; Sun et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of pollutants in the flue gas is based on there being 6 Vol.% O 2 in the flue gas and this is expressed in mg/Nm 3 (on the dry basis). Detailed descriptions are available in the references (Wang et al , 2016; Sun et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (2016) observed the effects of air distribution (excess ratio of primary air [ERPA]; excess ratio of secondary air [ERSA]; and excess ratio of total air [ERTA]) on furnace temperatures and on CO/NO/N 2 O/SO 2 emissions. They were studied systematically in a 0.2 MW lab-scale CFB furnace cofiring both biomass/coal and petroleum coke/coal.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic emissions of nitric oxide and carbon monoxide are a serious threat to human health and ecosystems. [1][2][3] Since both molecules can be co-reacted over noble metal-based catalysts [4] or perovskite-type metal oxide materials [5] into N 2 and CO 2 , considerable efforts have been devoted to the development of suitable catalytic materials for the reduction of NO with CO. In the early stage, platinum catalysts were studied in terms of support effects [6][7][8][9] and surface analysis using FT-IR.…”
Section: Introductionmentioning
confidence: 99%